Review of 20 years of research on microwave and millimeter-wave lenses at “Instituto de Telecomunicações” - Fernandes, C. A. (2015)
Starting from a challenge in the early 1990s to develop a highly shaped beam dielectric lens antenna for a pilot 150 Mb/s cellular mobile broadband system operating in the 60-GHz band, several new developments have been accomplished over more than 20 years at Instituto de Telecomunicações [1] in the areas of millimeter-wave shaped dielectric lens antennas and planar metamaterial lenses. We review here a few representative examples with numerical and experimental results, covering applications in mobile broadband communications, radiometry, satellite communications, multigigabit short-range communications, and sublambda near-field target detection.